2004
DOI: 10.1007/s11094-005-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physicochemical characteristics and pharmacokinetic parameters of 1,4-benzodiazepine derivatives

Abstract: A rational targeted search for new effective drugs of the benzodiazepine group should be based on established relationships between the physicochemical properties of compounds and their pharmacological activity, the direction and rate of biotransformation, and the pharmacokinetic parameters [1]. Correlations between these factors make possible drawing reliable judgments about the rate of absorption from the gastrointestinal tract, the time of attaining maximum concentration in the blood, the time of circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A similar finding was reported on the anti-MRSA of T. avicennioides; though, the leave part of the plant was used, but was found to be potent against MRSA isolated from Primary School Pupils in Ekiti State, Nigeria (Ajibade and Akinruli, 2016).This is an indication that harnessing T. avicennioides is advancement of the search for novel and viable anti-MRSA agent.The possible mechanism of action of the bioactive fraction of the extract against the test organism, MRSA, may be deduced from the presence of the functional groups. Previous studies (Hollosy et al, 2002;Litvin et al, 2004) indicated that halogen substituents on aryl rings resulted in compound with improved biological activity, hence, incorporation of halogen atoms into drug candidates have generally been correlated with increased lipophilicity; this enhances the penetration of agents into cells through the lipid membrane. The alkyl halides in the bioactive fractions may have explained the bactericidal mechanism of action of the agent against the MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported on the anti-MRSA of T. avicennioides; though, the leave part of the plant was used, but was found to be potent against MRSA isolated from Primary School Pupils in Ekiti State, Nigeria (Ajibade and Akinruli, 2016).This is an indication that harnessing T. avicennioides is advancement of the search for novel and viable anti-MRSA agent.The possible mechanism of action of the bioactive fraction of the extract against the test organism, MRSA, may be deduced from the presence of the functional groups. Previous studies (Hollosy et al, 2002;Litvin et al, 2004) indicated that halogen substituents on aryl rings resulted in compound with improved biological activity, hence, incorporation of halogen atoms into drug candidates have generally been correlated with increased lipophilicity; this enhances the penetration of agents into cells through the lipid membrane. The alkyl halides in the bioactive fractions may have explained the bactericidal mechanism of action of the agent against the MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the well‐known benzodiazepines, herein referred to as classic benzodiazepines, have comparatively high values for lipophilicity and can therefore partition with ease across cellular membranes and accumulate in areas of the body that are high in lipids . Furthermore, benzodiazepines also have high volumes of distribution (V d ) such as diazepam with a V d at steady state of 0.88–1.39 L kg −1 . The lipophilicity (as log P) of some NPS‐benzodiazepines has already been published in literature …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Furthermore, benzodiazepines also have high volumes of distribution (V d ) such as diazepam with a V d at steady state of 0.88-1.39 L kg −1 . [20][21][22][23] The lipophilicity (as log P) of some NPS-benzodiazepines has already been published in literature. 24 The acid-base dissociation constant (pK a ) of a compound is typically investigated during pharmaceutical development and plays an important role when used in conjunction with other parameters, such as molecular weight and lipophilicity.…”
Section: Introductionmentioning
confidence: 99%